Influence of the Yarkovsky effect on mean motion resonances of asteroids with small perihelion distances - Galushina, T. Yu; Letner, O. N.; Syusina, O. M.; Niganova, E. N. (Russian physics journal)
The paper studies the influence of the Yarkovsky effect on the resonant characteristics of asteroids with small perihelion distances. Out of 52 objects under study, 27 asteroids were identified that move in the vicinity of stable and unstable low-order mean motion resonances with major planets. The evolution of the asteroid orbits is constructed with and without allowance for the Yarkovsky effect, and the behavior of the resonance characteristics is analyzed in both cases. The effect was taken into account by including the perturbation from the transversal acceleration A(2), the values of which for the objects under study were obtained previously by the authors of this work. It is shown that the influence of the Yarkovsky effect on the stable resonances is insignificant and leads to small changes in the libration amplitude of the resonance characteristics. The stability of the resonance is preserved. For the unstable resonant interaction, the number of passages through the exact commensurability changes, and for some asteroids, the resonance becomes more stable.